2015
DOI: 10.1097/01.ogx.0000469196.99143.92
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-Gaze Positive Loop and the Coevolution of Human-Dog Bonds

Abstract: Mutual gaze is the most fundamental manifestation of social bonding in humans between mothers and infants and between sexual partners in monogamous species. Dog-to-owner gaze probably evolved as a form of social communication during domestication with humans, leading to the establishment of a human-dog bond that is similar to a mother-infant relationship. Urinary oxytocin increases in mothers following mutual gaze in both mothers and infants. A rise in urinary oxytocin occurs in dogs following mutual gaze, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(175 citation statements)
references
References 0 publications
7
164
1
3
Order By: Relevance
“…Recently, it was shown that OXT enables pup retrieval behavior in female mice by amplifying pup call responses in maternal auditory cortex (21). Furthermore, OXT has been implicated in maternal licking and grooming in rats (22), social affiliation of dogs toward their owners (23), and grooming of nonbond partners in chimpanzees, thus providing a cross-species mechanism that enables long-term cooperative relationships between kin and nonkin mammals (24). Notably, the OXT system not only plays a pivotal role in the formation and maintenance of pair bonds but is also affected by their disruption.…”
Section: Oxytocin and Social Attachment In Nonhuman Speciesmentioning
confidence: 99%
“…Recently, it was shown that OXT enables pup retrieval behavior in female mice by amplifying pup call responses in maternal auditory cortex (21). Furthermore, OXT has been implicated in maternal licking and grooming in rats (22), social affiliation of dogs toward their owners (23), and grooming of nonbond partners in chimpanzees, thus providing a cross-species mechanism that enables long-term cooperative relationships between kin and nonkin mammals (24). Notably, the OXT system not only plays a pivotal role in the formation and maintenance of pair bonds but is also affected by their disruption.…”
Section: Oxytocin and Social Attachment In Nonhuman Speciesmentioning
confidence: 99%
“…Facial perception, including eye gaze, plays an important role in inter-personal communication and social attachment in humans. 8,9,33,34 The ability of owners to gaze into their dog's eyes has been shown to promote the human-animal bond. 8 The hormone oxytocin regulates social bonding in humans.…”
Section: Separation Anxietymentioning
confidence: 99%
“…Reasons may include: fear of the risks of anesthesia, post-operative aesthetics, the ability of the dog or owners to cope post-operatively, concerns of the impact on welfare and quality of life, and the impact on the human-canine bond as eye contact is a key communicative technique between owner and dog. 8,9 While it is essential to educate owners about the enucleation procedure and the reasons for performing it, it is equally important that owners have a clear expectation of the post-operative recovery and appearance of their pet. Although as veterinary surgeons we may have a positive understanding of this procedure, we often do not have the experience of an owner in a home environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in presenting information on certain prehistoric specimens from the state of Idaho, Barbara Lawrence (1967: 47) referred to that trait as "this most doglike of all characters." The development of that trait may well have affected visibility (see McGreevy et al, 2004;Morey, 2010: 193), promoting the interspecific mutual gazing behaviors that are now known to characterize people and their dogs (Nagasawa et al, 2015). In any case, that trait certainly qualifies as part of Hare et al's (2012) domestication syndrome with respect to dogs.…”
Section: The Self-domestication Modelmentioning
confidence: 96%